RESEARCH OF ENTREPRENEURIAL BUSINESS INNOVATIONS IN TIMES OF CRISIS - Kyurova, Vyara; Davidkova, Blagovesta (Revista Inclusiones, 2020)
The article presents the results of a study of the preparedness of the entrepreneurial business in Bulgaria to innovate in times of crisis. The aim is to clarify the specifics of innovations, their role in the successful development of an entrepreneurial business and to outline the main problems. The assessment of the entrepreneurial business for innovations before and during the crisis is based on the results of a survey among 41 representatives of this business in Bulgaria. The theoretical aspects of innovation are discussed. Based on the survey, the main problems of the entrepreneurial business related to the implementation of innovations in a crisis are identified.